Bioinspired Materials for Energy Storage. Issue 2 (26th December 2021) - Mei, Jun; Liao, Ting; Peng, Hong; Sun, Ziqi
Abstract: Nature offers a variety of interesting structures and intriguing functions for researchers to be learnt for advanced materials innovations. Recently, bioinspired materials have received intensive attention in energy storage applications. Inspired by various natural species, many new configurations and components of energy storage devices, such as rechargeable batteries and supercapacitors, have been designed and innovated. The bioinspired designs on energy devices, such as electrodes and electrolytes, have brought about excellent physical, chemical, and mechanical properties compared to the counterparts at their conventional forms. In this review, the design principles for bioinspired materials ranging from structures, synthesis, and functionalization to multi‐scale ordering and device integration are first discussed, and then a brief summary is given on the recent progress on bioinspired materials for energy storage systems, particularly the widely studied rechargeable batteries and supercapacitors. Finally, a critical review on the current challenges and brief perspective on the future research focuses are proposed. It is expected that this review can offer some insights into the smart energy storage system design by learning from nature. Abstract : In this review, the design principles for bioinspired materials in terms of structures, synthesis, functionalization, and integration for advanced energy storage systems, including rechargeable batteries and supercapacitors, are discussed. The bioinspired designs on cell configurations, electrodes, and electrolytes have brought about many excellent physical, chemical, and mechanical properties.